THE INFLUENCE OF THE WHISTLEBLOWING SYSTEM ON FRAUD DETECTION IN EFFORTS TO ERADICATE CORRUPTION - Sandari, Tries Ellia (JEA17: Jurnal Ekonomi Akuntansi, 2022)
This study aims to determine the influence of whistleblowing systems, professional expertise, fraud auditors on fraud detection on efforts to eradicate corruption in government agencies in Indonesia. Populace from the study is all forensic auditors in government agencies and private companies, while the sample used is 100 investigators in government agencies who have a whistleblower system in their agencies. The research method carried out was to analyze using PLS using five variables, namely Whistleblowing System (X1), Professional Expertise (X2), Fraud Detection (Z), and Efforts to Eradicate Corruption (Y). The results of the study from pls grouped the variables of whistleblowing system, professional expertise, fraud auditors influential and significant on fraud detection variables and also variables of efforts to eradicate corruption crimes, while fraud detection variables have an effect and are significant on efforts to eradicate corruption in agencies-instanthe government in Indonesia.